(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Women entrepreneurship is a vital source not only for the economic development of a country but can also act an influential instrument to break off the fetters that existed owing to the extremely pervasive gender dissimilarities, especially when it comes to their workforce participation. And given that India’s route has progressively been shifting from women’s development to women-led development, there is a lot that the above-mentioned systems can do in terms of identifying uncultivated talents, provide necessary training and simplify inclusive role in industries, which can further subsidize towards growing industrial and national efficiency.